An interdisciplinary engagement with the human dignity of the sexual minorities in Grace Bible Church, Soweto : a case study on gender, law and religion - Sewapa, Tebogo Molate (Stellenbosch : Stellenbosch University, 2019)
Thesis (MTh)--Stellenbosch University, 2019.